Baseline plasma corticosterone, haematological and biochemical results in nesting and rehabilitating loggerhead sea turtles (Caretta caretta). - Romero, L. Michael.; Flower, Jennifer E.; Norton, Terry M.; Andrews, Kimberly M., 1978-; Nelson, Steven E., Jr.; Parker, Clare E.; Mitchell, Mark A., 1967- (Tufts University. Tisch Library., 2016)
The evaluation of hormonal responses to stress in reptiles relies on acquisition of baseline corticosterone concentrations; however, the stress associated with the restraint needed to collect the blood samples can affect the results. The purpose of this study was to determine a time limit for the collection of blood samples to evaluate baseline corticosterone, haematological and biochemical results in nesting (n = 11) and rehabilitating (n = 16) loggerhead sea turtles (Caretta caretta) Blood samples were collected from the dorsal cervical sinus of each turtle immediately after touching the animal (t0; 0-3 min) and 3 (t3; 3-6 min), 6 (t6; 6-9 min; nesting turtles only), 10 (t10; 10-13 min) and 30 min (t30; rehabilitating turtles only) after the initial hands-on time. Consistent between the rehabilitating and nesting turtles, there was a subtle yet significant increase in white blood cell counts over time. Despite the fact that white blood cell counts increased during the sampling period, there was no direct correlation between white blood cell count and corticosterone in the sampled turtles. In the nesting turtles, significant elevations in corticosterone were noted between t0 and t3 (P = 0.014) and between t0 and t6 (P = 0.022) Values at t10 were not significantly different from those at t0 (P = 0.102); however, there was a trend for the corticosterone values to continue to increase. These results suggest that sampling of nesting loggerhead sea turtles within 3 min of handling will provide baseline corticosterone concentrations in their natural environment. Significant elevations in corticosterone were also noted in the rehabilitating loggerhead sea turtles between t0 and t10 (P = 0.02) and between t0 and t30 of sampling (P = 0.0001) These results suggest that sampling of loggerhead sea turtles within 6 min of handling should provide baseline corticosterone concentrations in a rehabilitation setting. The delay in the corticosterone response noted in the rehabilitating turtles may be associated with the daily contact (visual or direct) they have with their human caretakers.